2011
DOI: 10.2106/jbjs.j.01597
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Randomized Trial Comparing Nonoperative Treatment with Volar Locking Plate Fixation for Displaced and Unstable Distal Radial Fractures in Patients Sixty-five Years of Age and Older

Abstract: At the twelve-month follow-up examination, the range of motion, the level of pain, and the PRWE and DASH scores were not different between the operative and nonoperative treatment groups. Patients in the operative treatment group had better grip strength through the entire time period. Achieving anatomical reconstruction did not convey any improvement in terms of the range of motion or the ability to perform daily living activities in our cohorts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
389
5
13

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 452 publications
(448 citation statements)
references
References 23 publications
15
389
5
13
Order By: Relevance
“…This use of overall clinical impression to guide decision making may have optimized results for both groups but the overall similarity in outcomes between patient groups (surgery versus nonoperative treatment and union versus malunion) are consistent with results from the randomized trials of Arora and Roumen. 10,23 In our series we were unable to identify any threshold for radiographic parameters beyond which poor function was expected. However, that does not preclude the possibility that such a threshold exists.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…This use of overall clinical impression to guide decision making may have optimized results for both groups but the overall similarity in outcomes between patient groups (surgery versus nonoperative treatment and union versus malunion) are consistent with results from the randomized trials of Arora and Roumen. 10,23 In our series we were unable to identify any threshold for radiographic parameters beyond which poor function was expected. However, that does not preclude the possibility that such a threshold exists.…”
Section: Discussionmentioning
confidence: 61%
“…Arora et al conducted a randomized trial comparing nonoperative treatment to volar locking plate fixation in 73 patients ≥65 years old with displaced and unstable DRF’s. 23 They demonstrated that although surgery improved radiographic parameters and increased grip strength it did not improve range of motion, pain, or patient-rated outcome at 1 year, and was associated with significantly more complications. Roumen et al evaluated DRF’s in patients ≥55 initially treated with closed reduction and casting.…”
Section: Discussionmentioning
confidence: 97%
“…Recent RCTs have not identified clear recommendations for the optimal treatment in the elderly population 30–32. In a systematic review cast immobilisation had the worst radiographic outcome but the least complications and a comparable functional outcome with surgical treatment options 31. Radiographic alignment after closed reduction and the functional demand of the patient should guide the decision for further operative stabilisation 29…”
Section: Recommendationsmentioning
confidence: 99%
“…Although the role of fracture displacement in the nonoperative treatment of distal humeral fractures remains unknown, the literature on the treatment of distal radial fractures in the elderly would support the observation that radiographic findings do not correlate with clinical outcomes. 2,9,11 The distal humerus is composed of medial and lateral columns that support the articular segment, which functions as a tie arch. 18 In our study, most of the articular fractures showed some degree of secondary congruence even in the presence of a significant articular step.…”
Section: Discussionmentioning
confidence: 99%